Implementasi Program Kredit Ketahanan Pangan dan Energi (Studi KKP-E di Desa Tanjungrejo Kabupaten Madiun) - Kurniaevani, Bremy (Jurnal Administrasi Publik, 2016)
Abstract: Implementation of the Food Security Credit Program and Energy (the CTF-E Programs Studies in Tanjungrejo village of Madiun County) Research in this thesis with purpose to describe from the Credit Program Implementation Food and Energy in the Tanjungrejo Village Madiun County. CTF-E is an intangible capital credit for the work needs to ranchers and small farmers. In the Tanjungrejo Village itself before the credit program food security and energy (CTF-E) own people have insufficient income from the farm. This program seeks to develop cattle breeding process to improve people’s lives by promoting cooperation among all stakeholders (Banking, Government, and Society). Implementation of Credit Program Food Security and Energy ( CTF-E) is composed of the involvement of actors, resources, communication between all the elements and objectives in this program. So economically beneficial to farmers so as to meet the needs of clothing, food and shelter them. While socially visible for mutual aid society. Keywords: implementation of a credit Program of food security and energy ,CTF-E, banking, ranchers, farmers, community groups.Abstrak: Implementasi Program Kredit Ketahanan Pangan dan Energi (Studi KKP-E di Desa Tanjungrejo Kabupaten Madiun)Penelitian yang dilakukan pada skripsi ini dengan tujuan untuk mendeskripsikan dari Implementasi Program Kredit Ketahanan Pangan dan Energi di Desa Tanjungrejo Kabupaten Madiun. KKP-E ini merupakan modal yang berwujud kredit untuk kebutuhan kerja kepada peternak maupun petani kecil.di Desa Tanjungrejo Kabupaten Madiun itu sendiri sebelum adannya program KKP-E masyarakatnya masih mempunyai penghasilan yang kurang dari memadai dari hasil peternakan. Maka program ini berupaya untuk mengembangkan proses peternakan sapi untuk meningkatkan taraf hidup masyarakat dengan menjalin kerja sama antar semua stakeholder (Perbankan, Pemerintah, serta Masyarakat). Implementasi Program Kredit Ketahanan Pangan dan Energi (KKP-E) ini terdiri dari keterlibatan aktor, sumberdaya, komunikasi antar semua elemen, dan sasaran dalam program ini.Jadi secara ekonomi bermanfaat bagi para peternak sehingga dapat memenuhi kebutuhan sandang, pandan dan papan mereka.Sedangkan secara sosial terlihat adanya gotong royong masyarakat. Katakunci: implementasi, kredit, KKP-E, perbankan, peternak, petani, kelompok tani, masyarakat.Abstract: Implementation of the Food Security Credit Program and Energy (the CTF-E Programs Studies in Tanjungrejo village of Madiun County) Research in this thesis with purpose to describe from the Credit Program Implementation Food and Energy in the Tanjungrejo Village Madiun County. CTF-E is an intangible capital credit for the work needs to ranchers and small farmers. In the Tanjungrejo Village itself before the credit program food security and energy (CTF-E) own people have insufficient income from the farm. This program seeks to develop cattle breeding process to improve people’s lives by promoting cooperation among all stakeholders (Banking, Government, and Society). Implementation of Credit Program Food Security and Energy ( CTF-E) is composed of the involvement of actors, resources, communication between all the elements and objectives in this program. So economically beneficial to farmers so as to meet the needs of clothing, food and shelter them. While socially visible for mutual aid society. Keywords: implementation of a credit Program of food security and energy ,CTF-E, banking, ranchers, farmers, community groups.